IL-1β-Induced Downregulation of the Multifunctional PDZ Adaptor PDZK1 Is Attenuated by ERK Inhibition, RXRα, or PPARα Stimulation in Enterocytes - Luo, Min; Yeruva, Sunil; Liu, Yongjian; Chodisetti, Giriprakash; Riederer, Brigitte; Menon, Manoj B.; Tachibana, Keisuke; Doi, Takefumi; Seidler, Ursula E. (Frontiers in Physiology, 2017)
Background: The PDZ adaptorprotein PDZK1 modulates the membrane expression and function of a variety of intestinal receptors and ion/nutrient transporters. Its expression is strongly decreased in inflamed intestinal mucosa of mice and IBD patients. Aim and Methods: We investigated whether the inflammation-associated PDZK1 downregulation is a direct consequence of proinflammatory cytokine release by treating intestinal Caco-2BBE cells with TNF-α, IFN-γ and IL-1β, and analysing PDZK1 promotor activity, mRNA and protein expression. Results: IL-1β was found to significantly decrease PDZK1 promoter activity, mRNA and protein expression in Caco-2BBE cells. A distal region of the hPDZK1 promoter was identified to be important for basal expression and IL-1β-responsiveness. This region harbours the retinoid acid response element RARE as well as binding sites for transcription factors involved in IL-β downstream signalling. ERK1/2 inhibition by the specific MEK1/2 inhibitors PD98059/U0126 significantly attenuated the IL-1β mediated downregulation of PDZK1, while NF-kappaB, p38 MAPK, and JNK inhibition did not. Expression of the nuclear receptors RXRα and PPARα was decreased in inflamed colonic-mucosa of ulcerative colitis patients and in IL-1β-treated Caco2-BBE cells. Moreover, the RAR/RXR ligand 9-cis retinoic acid and the PPARα-agonist GW7647 stimulated PDZK1 mRNA and protein expression and attenuated IL-1β-mediated inhibition. Conclusions: The strong decrease in PDZK1 expression during intestinal inflammation may be in part a consequence of IL-1β-mediated RXRα and PPARα repression and can be attenuated by agonists for either nuclear receptor, or by ERK1/2 inhibition. The negative consequences of inflammation-induced PDZK1 downregulation on epithelial transport-function may thus be amenable to pharmacological therapy.